2017
DOI: 10.1063/1.5009041
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of non-Markovian coarse-grained models employing the Mori–Zwanzig formalism and iterative Boltzmann inversion

Abstract: We propose a new coarse-grained (CG) molecular simulation technique based on the Mori-Zwanzig (MZ) formalism along with the iterative Boltzmann inversion (IBI). Non-Markovian dissipative particle dynamics (NMDPD) taking into account memory effects is derived in a pairwise interaction form from the MZ-guided generalized Langevin equation. It is based on the introduction of auxiliary variables that allow for the replacement of a non-Markovian equation with a Markovian one in a higher dimensional space. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Lei et al [71] subsequently demonstrated that a fictitious particle approach can be more rigorously connected to the GLE representation through a rational function approximation of the Laplace transform of the memory kernel. More recently, Karniadakis and coworkers [40,72] have pursued a similar auxiliary variable approach, to simplify the implementation of non-Markovian DPD. Although these studies consider models with coarser representations (one site for a cluster of Lennard-Jones particles or an entire star polymer), the results contain potentially useful lessons for coarse-graining at a higherresolution.…”
Section: E Friction Kernels With Memorymentioning
confidence: 99%
“…Lei et al [71] subsequently demonstrated that a fictitious particle approach can be more rigorously connected to the GLE representation through a rational function approximation of the Laplace transform of the memory kernel. More recently, Karniadakis and coworkers [40,72] have pursued a similar auxiliary variable approach, to simplify the implementation of non-Markovian DPD. Although these studies consider models with coarser representations (one site for a cluster of Lennard-Jones particles or an entire star polymer), the results contain potentially useful lessons for coarse-graining at a higherresolution.…”
Section: E Friction Kernels With Memorymentioning
confidence: 99%
“…( 6)). Different ways to consider the friction matrix were reported [19,47] as well as to include memory effects in CG simulations, [37,[76][77][78].…”
Section: Markovian Approximation Of the Memory Kernelmentioning
confidence: 99%
“…In the context of modelling soft matter, the method of extending the state space by auxiliary variables in order to obtain Markovian dynamics is also frequently used [52,189,190,53,171,46,54,191]. In particular, for coarse-grained polymer models, as described in sec.…”
Section: Steady States With Memorymentioning
confidence: 99%